The goal of research is to identify the effect of teaching means (multi-propose) Learn some basic skills in score for beginners (handling, containment, scoring). - Abood, Abedulameer (Journal of Physical Education, 2015)
he goal of research is to identify the effect of teaching means (multi-propose) Learn some basic skills in score for beginners (handling, containment, scoring). The sample consisted of numbers of beginners players in the Development Athletic Work Institute/ Karkh andtotaling24 players were divided into two groups and random method(12player) for the experimental group and (12 player) for the controlling groups. The experimental group worked with on the main teaching aid while the control group worked with the school’s coach to apply the Development Athletic Work Institute program. The researcher used three tests of skill codified skills to the test researched. After conducting themain test, which lasted for two consecutive months. The researcher held a posteriori test. After recording the result swere tabulated tables and subjected to statistic al treatments through the bag statistical SPSS, was concluded as follows: • The multi-propose teaching aid has a great effect on developing the basic Finally the researcher recommendations include the following: • The need to use learning tool (multi-propose)as a teaching tool to help facilitate and accelerate the learning of the beginners